The influence of digital diplomacy on the conduct of Kenya's foreign policy - Mutua, Lindah; Kinyua, Riungu Festus; Milui, Joshua (African Journal of Empirical Research, 2026)
The field of diplomacy has not been immune to the ongoing transformation in global communication brought about by digital technologies. Despite increasing use of digital diplomacy in Kenya’s foreign policy today, it is still unclear how it has influenced the country’s bilateral and multilateral diplomatic ties as well as the broad foreign policy pursuits. The study’s main objective was to explore the influence of digital diplomacy on the conduct of Kenya’s foreign policy. Specific objectives included the following: to assess the nature and type of digital diplomacy influencing Kenya’s bilateral and multilateral foreign policy, to examine the effectiveness of digital diplomacy strategies in Kenya’s foreign policy, and to evaluate the challenges and opportunities of digital diplomacy in Kenya’s foreign policy. The study was guided by soft power theory and public diplomacy theory and adopted a descriptive research design to answer the research questions. The study’s target population entailed 150 respondents comprising Kenya’s Ministry of Foreign Affairs officials, such as diplomatic, embassy & consulate staff; Ministry of Foreign Affairs social media managers, public relations officers, and information technology [IT] personnel; and civil society organization representatives. Stratified purposive sampling technique was used to select a sample size of 109, calculated using the Yamane formula. A structured questionnaire and key informant interview guide were used for data collection. Data analysis was done using descriptive, inferential, and thematic content analysis methods. Analyzed quantitative data was presented using tables and figures, whereas processed qualitative data was presented using narratives and direct quotes. The study revealed that Kenya has progressively adopted various digital diplomacy channels, such as social media, government websites, and virtual engagements, which have greatly improved its bilateral and multilateral relations. It was also established that Kenya's digital diplomacy strategies have been instrumental in supporting its foreign policy objectives such as raising its national profile globally, creating partnerships, and advancing national interests abroad. The study concluded that digital diplomacy is an increasingly significant and influential aspect of Kenya's foreign policy, especially when it comes to raising awareness, fostering bilateral relationships, and increasing involvement in multilateral forums. However, due to operational and structural challenges, its full potential is still untapped. As such, the study recommended policy reforms, institutional capacity-building, and strengthening two-way communication strategies to encourage digital innovation.